eDOBS - Graphical Debugging for Eclipse - Geiger, Leif; Zündorf, Albert (Electronic Communications of the EASST, 2007)
This paper presents the eDOBS tool. eDOBS is the little brother of the Fujaba environment. While Fujaba is used to create graph grammar based specifications and programs, eDOBS is used to browse graphs, to edit graphs, and to execute graph transformations.